AIAA/AAS Astrodynamics Specialist Conference and Exhibit 2002
DOI: 10.2514/6.2002-4421
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Thrust Version of the Aldrin Cycler

Abstract: In this paper we seek a low-thrust version of a cycler orbit between Earth and Mars known as the Aldrin cycler. The principal goal is to design trajectories that have low flyby V at both planets while minimizing the total propellant cost. Our research is aided by several powerful software tools, including a recently developed low-thrust optimizer. With these tools, we are able to produce several promising low-thrust versions of Aldrin cyclers. Our analysis shows that such cyclers can significantly reduce the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The final trajectories 23,25,26 presented in Table 2 belong to our second trajectory category where the tether sling launches a taxi vehicle to rendezvous with a vehicle in a cycler orbit. The Aldrin cycler consists of two cycler vehicles called an up-cycler and a downcycler.…”
Section: Tether Sling Performancementioning
confidence: 99%
“…The final trajectories 23,25,26 presented in Table 2 belong to our second trajectory category where the tether sling launches a taxi vehicle to rendezvous with a vehicle in a cycler orbit. The Aldrin cycler consists of two cycler vehicles called an up-cycler and a downcycler.…”
Section: Tether Sling Performancementioning
confidence: 99%
“…There need to be multiple Mars cyclers ("up" and "down" versions) and they will require Earth flybys and propulsion to keep their orbit synchronization with the orbit of Earth and Mars. Analyses have shown that efficient low thrust propulsion may be sufficient for this 14 . This cycler would enable a safe, comfortable and robust exploration of Mars, along with the establishment of a Mars outpost with large scale ISRU, thus providing the means to develop Biosphere II equivalent habitats on the Mars surface.…”
mentioning
confidence: 99%